Oncomodulin (OCM) uniquely regulates calcium signaling in neonatal cochlear outer hair cells. (July 2022) - Murtha, Kaitlin E.; Yang, Yang; Ceriani, Federico; Jeng, Jing-Yi; Climer, Leslie K.; Jones, Forrest; Charles, Jack; Devana, Sai K.; Hornak, Aubrey J.; Marcotti, Walter; Simmons, Dwayne D.
Highlights: Onset of oncomodulin expression occurs at postnatal day 3, which correlates with increased calcium buffering in cochlear outer hair cells Deletion of oncomodulin alters the expression patterns of α-parvalbumin and sorcin during early development of outer hair cells Oncomodulin and α-parvalbumin both contribute to OHC calcium homeostasis during early postnatal development Oncomodulin exhibits faster calcium-buffering compared to either α-parvalbumin or sorcin when transiently expressed in HEK293T cells Abstract: In cochlear outer hair cells (OHCs), a network of Ca 2+ channels, pumps and Ca 2+ -binding proteins (CaBPs) regulates the localization, spread, and magnitude of free Ca 2+ ions. During early postnatal development, OHCs express three prominent mobile EF-hand CaBPs: oncomodulin (OCM), α-parvalbumin (APV) and sorcin. We have previously shown that deletion of Ocm ( Ocm -/- ) gives rise to progressive cochlear dysfunction in young adult mice. Here, we show that changes in Ca 2+ signaling begin early in postnatal development of Ocm -/- mice. While mutant OHCs exhibit normal electrophysiological profiles compared to controls, their intracellular Ca 2+ signaling is altered. The onset of OCM expression at postnatal day 3 (P3) causes a developmental change in KCl-induced Ca 2+ transients in OHCs and leads to slower KCl-induced Ca 2+ transients than those elicited in cells from Ocm -/- littermates. We compared OCM buffering kinetics with other CaBPs in animal models and cultured cells. In a double knockout of Ocm and Apv ( Ocm -/- ;Apv -/- ), mutant OHCs show even faster Ca 2+ kinetics, suggesting that APV may also contribute to early postnatal Ca 2+ signaling. In transfected HEK293T cells, OCM slows Ca 2+ kinetics more so than either APV or sorcin. We conclude that OCM controls the intracellular Ca 2+ environment by lowering the amount of freely available [Ca 2+ ]i in OHCs and transfected HEK293T cells. We propose that OCM plays an important role in shaping the development of early OHC Ca 2+ signals through its inimitable Ca 2+ buffering capacity. Graphical Abstract: Image, graphical abstract